Understanding of TV Ads amongst Urban Children - Ahluwalia, Amardeep Kaur; Singh, Raghbir (Indian Journal of Marketing, 2012)
TV has long been the predominant medium that advertisers have chosen for reaching consumers to market products. Ads are an important experiential component of a child's development. This study was conducted to find out understanding of TV ads amongst children from middle and upper-middle socio-economic strata of the urban society. A sample of 400 children of 8 to 16 years of age, across the region of Punjab were selected. Almost all children claimed to differentiate between ads and programs. A majority of children clearly understood the purpose behind ads, though there was a better understanding amongst girls and older children. Children who watched TV in the presence of the elders could comprehend the ads better. Most of the parents discussed ads with their children only when they were asked by them, instead of taking initiative on their own. Parents discussed the implications of ads more often with girls and with older children.